Efficacy of BNT162b2 and CoronaVac in patients diagnosed with COVID-19 - Dogan Mustafa; Yilmaz Berna (Acta Pharmaceutica)
This retrospective observational study is aimed to determine the efficacy of BNT162b2 (Pfizer-BioNTech) and CoronaVac (Sinovac) vaccines against symptomatic or severe disease in COVID-19-diagnosed patients. The secondary aim was to define the differences between vaccinated and un-vaccinated patients in terms of age, comorbidities and course of the disease, and to determine the survival rates. Of the 1463 PCR-positive patients, 55.3 % were vaccinated, and 44.7 % were unvaccinated. While 959 patients had mild-moderate symptoms, 504 patients had severe-critical symptoms and were treated in the intensive care unit. There was a statistically significant difference in the distribution of the type and doses of vaccines between the patient groups (p = 0.021). The rate of receiving 2 doses of Biontech was 18.9 % in the mild-moderate patient group but lower in the severe patient group (12.6 %). The rate of two doses of Sinovac and two doses of Biontech vaccine (four doses of vaccine) was 5 % in the mild-moderate patient group and 1.9 % in the severe patient group. The mortality rates were statistically significantly different (p < 0.001) between the patient groups: 65.3 % in the severe patient group and 1 % in the mild-moderate patient group. The multivariate model showed that the mortality risk of the unvaccinated patients was 1.5 times higher than the vaccinated ones (p = 0.042). In addition to being unvaccinated, advanced age, coronary artery disease (CAD), diabetes mellitus (DM), chronic obstructive pulmonary disease (COPD), chronic kidney disease (CKD), and obesity were found to be associated with higher mortality risk. Besides, the reduction in mortality rate was more evident in individuals vaccinated with at least 2 doses of the BNT162b2 (Pfizer-BioNTech) vaccine than in CoronaVac group.